Characteristics and outcome of chronic inflammatory demyelinating polyradiculoneuropathy patients according to their diagnostic certainty based on the 2021 EAN/PNS criteria - Loser, Valentin; Vicino, Alex; Staedler, Katia; Kuntzer, Thierry; Théaudin, Marie (Journal of the neurological sciences, 2024)
To describe the clinical characteristics and long term outcome of CIDP patients according to 2021 EAN/PNS diagnostic certainty categories. We reviewed clinical data, response to treatment, cerebrospinal fluid examination, and nerve conduction studies parameters of 39 adult “CIDP” and 24 “possible CIDP” patients. Data were collected at diagnosis and after one (T1), two (T2), three (T3) and five years (T5). At diagnosis, “possible CIDP” patients' phenotypes were more atypical (especially focal/multifocal, p < .01) and “CIDP” patients had a higher NIS and INCAT scores (p = .08 and 0.08). Compared to baseline: median NIS score decreased in “CIDP” and was stable in “possible CIDP” patients at T1 (p < .05), T2 (p < .05) and T3 (p < .01); median MRC score slightly increased in “CIDP” and was stable in “possible CIDP” patients at T2 (p < .05); and INCAT disability scale slightly decreased in “CIDP” and was stable in “possible CIDP” patients at T3 (p < .05). The proportion of moderate to severely disabled (mRS > 2) patients in “possible CIDP” group was higher than in “CIDP” group (not significant). “CIDP” patients had a better objective response to immunotherapy (59 % responders) than “possible CIDP” patients (29 % responders, p < .05), especially among typical CIDP patients (86 % of responders in “CIDP” versus 33 % of responders in “possible CIDP” patients, p < .05). “CIDP” patients had a more severe neuropathy, estimated with the NIS and INCAT scores, and “possible CIDP” patients had a more atypical phenotype at baseline. Our data suggest that long-term patient outcome and response to immunotherapy is better in “CIDP” than “possible CIDP”. •EAN/PNS 2021 classify patients as “CIDP” or “possible CIDP”.•“CIDP” patients respond better to immunotherapy than “possible CIDP” patients.•Long term outcome seems better in “CIDP” patients.•“Possible CIDP”: axonal loss, misdiagnosis, diagnostic delay may explain poor outcome.